POLITENESS, SPEECH ACT, AND DISCOURE IN SASAK COMMUNITY - Muh. Junaidi (Balai Bahasa Nusa Tenggara Barat, 2017)
Politeness, speech act and discourse have become an interest area of language use in context. Attention has been drawn to the universality of politeness strategies across the culture. This study examines the nature of pattern of communication in terms of politeness, speech acts and discourse in Sasak speech community. The subject of the study is 1 Tuan Guru giving religious speech in Sikur village. Participant observation is used as the method of data collection in this study. A video recording was used to collect data. Result of the study shows that reminding and suggesting are not the acts of indicating or threatening addressees’ negative face, but positive strategies used to minimize the threat for addressees’ positive face and negative one as a means of saving addressees’ negative face. These three variables were interrelated to decipher the nature of speech pattern of language use in the Sasak speech community. The notion of face should be analyzed according to norms and cultural values of such acts in different speech communities. Hence, the universality of communicative action and the type of speech act in a given speech community are crucial variable to scrutinize the language use in context